El beneficio tributario de devolución de IVA a los sectores prioritarios y su incidencia en la redistribución de los ingresos del sector en el Ecuador. - Bonilla López, Fabricio Roberto (2021)
The research analyzes the fiscal effect that VAT refunds have on priority sectors (older adults and people with disabilities) and how these affects and impact the public policy of social action with the redistribution of income towards the priority sectors of the country, who They have tax exemptions established in the legal regulations. As part of the methodology, mixed research methods and quantitative analysis were used, based on surveys applied to 470 older adults and 470 disabled people from vulnerable sectors. Based on these results and the information collected, it was analyzed by the analytical method and descriptive and inferential statistics. The present investigation showed as the main result, that more than 80% of citizens who access the tax benefit are people with an average income above $ 637.00 (high income type A + Quintile 5) and improves the quality of life of citizens in vulnerability; but it does not guarantee a dignified life to citizens who are in poverty and extreme poverty, nor does it promote participation and a social ethic based on transparency and co-responsibility on the part of the State. The conclusion is that the benefit does not help eradicate extreme income poverty.